Prevalence of anemia and nutritional status among HIV-positive children receiving antiretroviral therapy in Harar, eastern Ethiopa - Teklemariam Z (Dove Medical Press, 2015)
Zelalem Teklemariam,1 Habtamu Mitiku,1 Firehiwot Mesfin2 1Department of Medical Laboratory Sciences, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 2School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia Purpose: Anemia and growth retardation are common manifestations of HIV-positive children, which threaten their lives. Therefore, this study tried to assess the burden of anemia and the nutritional status of HIV-positive children receiving antiretroviral therapy (ART) in eastern Ethiopa. Patients and methods: A total of 108 records of children on ART followed up in Hiwot Fana Specialized University Hospital from 2007 to 2010 were retrospectively reviewed from November 1 to November 30, 2011. Results: Approximately 54.4% of the children had been anemic before the initiation of their ART (at baseline): 7.8% were severely anemic and 44.7% were moderately anemic. These percentages were higher in preschool children than in school children (adjusted odds ratio [AOR]: 4.80 [95% confidence interval CI: 1.96, 11.75]), and were higher in males than in females (AOR: 2.61 [95% CI: 1.06, 6.45]). The prevalence of anemia was reduced to 39.2% 1 year after initiation of ART. The increasing of hemoglobin values was highly significant for both zidovudine (AZT)- and stavudine (d4T)-based ART (P<0.05). At baseline, 51.6% of the study subjects were underweight (weight-for-age Z score less than -2 standard deviation [SD]); 49.1% were stunted (height-for-age Z score less than -2 SD); and 31.5% were wasted (body mass index less than -2 SD), which, after a year on ART, declined to 8.9%, 15.9%, and 9.8%, respectively. Conclusion: There was high prevalence of anemia and growth failure among HIV-infected children in the study area. However, there was a decline after initiation of ART. Therefore, adherence counseling to strengthen the uptake of ART is recommended. Moreover, large-scale, prospective studies should be done to understand the magnitude and etiology of the problems with HIV-negative control groups. Keywords: hemoglobin, underweight, stunting, wasting